2015
DOI: 10.1016/j.jtumed.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of total quality management in hospitals

Abstract: Objectives: The aims of the study were to explore the extent of Total Quality Management (TQM) implementation in hospitals and its association with demographic variables.Methods: This cross-sectional study collected data from 332 nurses using a self-developed questionnaire. The participants were recruited from government, military, university and private health sectors. Results:The results of this study showed that 70% of variance in implementing TQM can be achieved by following the principles of TQM. These pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 9 publications
5
18
0
5
Order By: Relevance
“…Similar report was obtained from focus group respondents who mentioned that there were policies in place in the hospital to ensure proper implementation of TQM in the hospital but the management had failed to put it to maximum use. This finding supports what Breedlove et al [20], Balasubramanian and Al-Shdaifat observed, that the hospital management needs to lead the total quality process and also encourage others within the healthcare institution to follow and prove to them that management means what they say about quality [21,22]. Nonetheless, the findings contrasted with what Skiti reported on the average score on the manner the management have implemented the organizational mission, vision, short and long term goals [23].…”
Section: Organizational Factorssupporting
confidence: 83%
See 1 more Smart Citation
“…Similar report was obtained from focus group respondents who mentioned that there were policies in place in the hospital to ensure proper implementation of TQM in the hospital but the management had failed to put it to maximum use. This finding supports what Breedlove et al [20], Balasubramanian and Al-Shdaifat observed, that the hospital management needs to lead the total quality process and also encourage others within the healthcare institution to follow and prove to them that management means what they say about quality [21,22]. Nonetheless, the findings contrasted with what Skiti reported on the average score on the manner the management have implemented the organizational mission, vision, short and long term goals [23].…”
Section: Organizational Factorssupporting
confidence: 83%
“…The respondents with tertiary education believed that quality personnel were inadequate in the hospital but that the quality of services which the hospital rendered to the public was good, similar to what Chakrabusty et al and Shehu et al reported indicating that majority were satisfied with physicians' courtesy, attention to complaints, patience with them, explanation of what they wanted to know and providing them with good advice and treatment [31,32]. There was insufficient supervision of staff in the hospital on the implementation of TQM, especially among those that had spent less than ten years in the facility, this is similar to what Anyansi [34] reported in Ebonyi state, Balasubramanian in India and Al-Shdaifat [21,22].…”
Section: Interpersonal Factorssupporting
confidence: 52%
“…More importantly, only a few previous studies have attempted to evaluate the implementation of TQM and its effects in different sectors, for instance in public hospitals (Al-Shdaifat, 2015); telecommunication (Dada and Eniola, 2018); education (Ogunnaike et al., 2014), and the construction industry (Samuel Oludare and Olugboyega, 2016), while there is very limited or no empirical study specifically focusing on the relationship with organizational performance. Hence, this investigation purposes is to add to the research in the newer context of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of care is a major issue for healthcare facilities that they are required to improve in order to comply with standards and to meet patients' needs [38]. Patient satisfaction is one of the important indicators of quality of care.…”
Section: Discussionmentioning
confidence: 99%